Modeling the spatiotemporal effects of ocean acidification and warming on Atlantic sea scallop growth to guide adaptive fisheries management - Halle M. Berger; Samantha A. Siedlecki; Shannon L. Meseck; Emilien Pousse; Deborah R. Hart; Felipe Soares; Antonie Chute; Catherine M. Matassa (Ecological Modelling, 2026)

Correction: Refining the Farm Aquaculture Resource Management Model for Shellfish Nitrogen Removal at the Local Scale - Skylar R. Bayer; Alhambra M. Cubillo; Julie M. Rose; Joao G. Ferreira; Mark Dixon; Annita Alvarado; Janine Barr; Genevieve Bernatchez; Shannon Meseck; Matthew Poach; Emilien Pousse; Gary H. Wikfors; et al. (Estuaries and Coasts, 2024)

Refining the Farm Aquaculture Resource Management Model for Shellfish Nitrogen Removal at the Local Scale - Skylar R. Bayer; Alhambra M. Cubillo; Julie M. Rose; Joao G. Ferreira; Mark Dixon; Annita Alvarado; Janine Barr; Genevieve Bernatchez; Shannon Meseck; Matthew Poach; Emilien Pousse; Gary H. Wikfors; et al. (Estuaries and Coasts, 2024)
Nutrient-related environmental degradation in coastal waters is a continuing global problem. Bivalve shellfish farms show nutrient removal capabilities similar to some traditional management strategies and in some places have been incorporated into nutrient management programs to help achieve water quality goals. Bioextractive nutrient removal varies by farmed species and is influenced by environment parameters; thus, data and information for both are needed to estimate nutrient mitigation potential of shellfish farms. The Farm Aquaculture Resource Management (FARM) model, calibrated for farmed species, uses local environmental and farming practice data to simulate interactions between the farmed population and the local environment and to optimize cultivation practices for economic gain. We calibrated the model to predict nitrogen removal by Eastern oyster ( Crassostrea virginica ) farms with specific field and experimental data on oysters, their local environment, and farm practices in Long Island Sound, CT, USA. Previous FARM applications were not validated for nitrogen removal with local data. In the harvest when ready (HWR) model scenario (oysters are harvested when they reach harvest size), the farm removed 159 kg N ha −1 year −1 while the non-HWR scenario (all oysters are harvested at one time) removed 274 kg N ha −1 year −1 . These estimates are within the range of previously reported in-water bioextraction studies in the Northeastern USA. The robust outputs from this validated model can be reliably used in marine spatial planning efforts and by nutrient managers to predict the nitrogen removal benefits that could be achieved through new or expanded eastern oyster farms in eutrophic environments.